Application of quality control circle activities to improve the implementation rate of prevention on deep venous thrombosis in patients undergoing urological surgery (提高泌尿外科手术患者深静脉血栓形成预防措施落实率的品管圈实践) - QIU Deyuan (仇德媛); DUAN Junfang (段俊芳); LI Ping (栗平); QIN Xiaocui (秦晓翠); WANG Huihui (王惠惠); ZHANG Yingying (张莹莹); CHEN Menghan (陈孟涵) (中西医结合护理)
Objective To explore the application effect of quality control circle (QCC) activities in improving the implementation rate of deep vein thrombosis (DVT) prevention in patients undergoing urological surgery. Methods From July 2020 to December 2020, 125 cases of urology surgery patients with lack of management of DVT were investigated. The causes were analyzed according to the investigation results, and the improvement plan was established and implemented based on evidence. The implementation condition of DVT prevention in another 125 cases of urology surgery patients was evaluated after QCC activities. Results The implementation rate of DVT prevention increased from 62. 40% before implementation of QCC activities to 97. 60％ after implementation of QCC activities, with a significant difference (P<0. 05). Conclusion Application of QCC management tool can improve the management standard of DVT prevention in patients undergoing urological surgery and effectively reduce the incidence of DVT. (目的 探讨运用品管圈质量管理工具提高泌尿外科手术患者深静脉血栓形成(DVT)预防措施落实率的效果 。方法 对2020年7月—12月(实施前)泌尿外科125例手术患者深静脉血栓管理缺失现状进行调查, 根据调查结果进行原因分析, 通过循证制定改进方案并实施。 对2021年1月—6月(实施后)125例泌尿外科手术患者DVT预防措施落实情况进行分析。结果 DVT预防措施落实率由品管圈活动实施前的62. 40%提升至实施后的97. 60％, 差异有统计学意义(P＜0. 05)。结论 应用品管圈质量管理工具开展DVT预防, 管理工作更加规范, 提高DVT预防措施落实率, 对效降低患者的DVT的发生风险具有积极意义。)